Hubungan Pengetahuan dengan Kecemasan Ibu Pasca Imunisasi DPT Anaknya di Kelurahan Kolakaasi - Bangu Bangu; Yuhanah Yuhanah (Jurnal Surya Medika (JSM), 2020)
Immunization is an injection of immunity against certain diseases. The disease is avoided by means of a complete basic immunization in infants before 1 year of age. A report from the section on eradicating infectious diseases in the Ministry of Health in Indonesia has decreased the number of people who can be prevented by immunization programs. The success of this program is the collaboration between the immunizers and Posyandu cadres supported by the government and awareness from the community. Ignorance of mothers about DPT immunization is a major cause of anxiety in mothers after DPT immunization in their children. The materials and methods used were knowledge questionnaire sheets and maternal anxiety levels. This type of research is an analytic survey. The survey method uses cross-sectional. The population was 183 mothers as respondents. The results obtained by knowledge of high category mothers while anxiety categories are low. Analysis of the data with the Spearman Rho technique, the results obtained were 0.658 significant. Towards 0.01. Test results get = 0,000 means there is a significant relationship between knowledge and anxiety. Conclusion: The higher the knowledge, the lower the anxiety level of mothers after immunizing the DPT to their children in the Kolakaasi Village.